AN ANALYSIS OF VALUES IN ANNA KARENINA NOVEL WITH REPRESENTATION OF ANNA KARENINA’S CHARACTER - Rahmat Fajar (English Language, Linguistics, Literature, And Education Journal, 2023)
This study analyzes the values ​​contained in the novel entitled "Anna Karenina". Where in the novel contains the elements of values ​​that are analyzed are individual values ​​and social values. The aims of this research are (1) to analyze what individual values ​​are contained in the novel “Anna Karenina” (2) to analyze what social values ​​are contained in the novel “Anna Karenina” (3) to compare the values individual and social values ​​contained in the novel "Anna Karenina". Researchers uses descriptive analysis method in conducting this research. The researcher uses a qualitative research method design as a research design. In this research, the researcher uses the theory of sociology of literature, the theory of individual values ​​and social values. The source of the data in this study is the novel "Anna Karenina" in 1877 by Leo Tolstoy. From the results of this research, based on the theory of Individual Basic Values ​​from Schwartz, the researcher found 10 individual values ​​owned by the Anna Karenina’s character, based on the characteristics put according by Durkehim, the researcher found social values, then the researchers found a comparison of individual values ​​to social values, including comparisons power values ​​with social values, hedonism values ​​with social values, and a comparison of self-direction values ​​with social values.